"The significance of the GNRH 1 gene polymorphism (rs 6185, rs1812594) in the development of idiopathic hypogonadotropic hypogonadism." (Texas Journal of Medical Science, 2024)
The purpose of the study is to study the significance of the GNRH 1 gene polymorphism (rs 6185, rs1812594) in the development of idiopathic hypogonadotropic hypogonadism in boys and girls.